Effect in Pain Scale of Trocar Insertion, Onset, and Duration of Anesthesia of Subtenon Anesthesia without Premedication Compared with Premedication in Pars Plana Vitrectomy: A Randomized Controlled Trial - Andayani, Ari; Agrasidi, Putu Anindya; Sutyawan, I Wayan Eka; Widiana, I Gde Raka; Widnyana, I Made Gede; Pemayun, Cok Istri Dewiyani (Greenation Publisher & Yayasan Global Research National, 2025)
Effect in Pain Scale of Trocar Insertion, Onset, and Duration of Anesthesia of Subtenon Anesthesia without Premedication Compared with Premedication in Pars Plana Vitrectomy: A Randomized Controlled Trial. Background: Pars plana vitrectomy (PPV) has traditionally been performed under general anesthesia. However, in recent years, regional anaesthetic techniques such as subtenon block have gained popularity due to their safety and effectiveness, reducing the risk of severe complications associated with needle-based blocks. Patients and Methods: This randomized controlled trial (RCT) was conducted between November 2023 to March 2024 at a tertiary teaching hospital in Indonesia. A total of 30 patients undergoing vitrectomy were randomized assigned to one of two groups: with premedication or without premedication. The primary outcomes evaluated were the pain scale during trocar insertion, the onset of anesthesia, and the duration of anesthesia. Statistical analyses were performed using the Mann-Whitney U test and ANCOVA. Results: No significant differences were observed between the two groups regarding the pain scale during trocar insertion, the onset of anesthesia, or the duration of anesthesia (p<0.001). However, after adjusting for diagnosis and type of the therapy, the group without premedication demonstrated a significantly longer duration of anesthesia. Conclusion: Subtenon anesthesia without premedication represents a viable alternative for pars plana vitrectomy. It offers practical benefits, such as eliminating the need for fasting and intravenous line placement, while maintaining patient and operator comfort.